(untitled) (Journal of Science and Technology, 2016)
An adequate supply of portable water is essential for socio-economic development. However, many people in developing countries especially Africa have inadequate water supplies. In many African countries, land degradation is increasing and water resources are under threat through rapid growth and urbanisation. Human activities such as poor agricultural practices, inappropriate domestic and industrial waste disposable methods and destruction of water sheds are exacerbating water pollution. Another area of concern is the danger of prolonged drought and over-exploitation of available ground water resources resulting of increasing population and urban sprawl, leading to the drastic fall in water levels with consequences of failing hand pumps, wells and water shortage in the urban and peri-urban areas. This paper examines the relationship between population dynamics and water supply in the peri-urban interface because the health, ecological and environmental problems facing poor households in the peri-urban areas are either directly or indirectly linked to population growth and urbanisation dynamics.